Endo-glucanase digestion of oat β-Glucan enhances Dectin-1 activation in human dendritic cells. (March 2016) - Sahasrabudhe, Neha M.; Tian, Lingmin; van den Berg, Marco; Bruggeman, Geert; Bruininx, Erik; Schols, Henk A.; Faas, Marijke M.; de Vos, Paul
Highlights: Enzyme digestion of oat β-Glucan increases its immune potential. The increased immune response of digested oat β-Glucan is through Dectin-1 receptor. Digested and nondigested oat β-Glucans do not differ in activation of Dectin-1A and Dectin-1B. Digested oat β-Glucan induced production of MCP-1, RANTES, IL-8, and IL-4 in human dendritic cells. The immune stimulation was dependent on exposed β-(1-3) linkages and particle size of β-Glucan. Abstract: Oat β-Glucans were studied for their immunological impact before and after enzymatic digestion in order to enhance the efficacy of oat β-Glucans for application in functional foods. Oat β-Glucan is reported to have minimal impact compared to its fungal counterpart in vitro . Digestion with endo-glucanase enhanced its efficacy towards stimulating MCP-1, RANTES, IL-8, and IL-4 production in human dendritic cells as compared to the nondigested β-Glucan. This effect resulted from an enhanced activation of the Dectin-1 receptor. Our data suggest that the immune-stimulation was dependent on the β-(1-3) linkages and the reduced particle size of digested β-Glucans. Thus, we show that enzymatic pre-digestion of dietary fibres such as oat β-Glucan enhances its impact on specific immune receptors. We also demonstrate that particle size and/or molecular weight of oat β-Glucans and exposure of specific binding sites for the receptors might be important tools for designing efficacious functional feed and food additives.